Optimizing Wheat Yield and Biomass for Bioenergy: A Comparative Study of Multi-Sowing Techniques for Sustainable and Eco-friendly Production (Journal of Agriculture and Biology, 2025)
Conventional tillage is more laborious, more time consuming and more water consuming for wheat production. On the other hand, zero tillage is less time, and less water consumed with minimum labor requirement. Zero tillage also has a lesser environmental impact as it reduces soil erosion, greenhouse gas emissions, and the overall consumption of resources such as fuel and water. In the rice wheat cropping system, there is minimum time available for sowing of wheat after the harvest of paddy rice. Due to delay in sowing wheat, losses of yield are 35 to 60 kg/day/ha. To increase the production of food and to meet the needs of food security are the key challenges for scientists. The demand for food is still increasing, not only to meet food security for a growing population, but also to provide more nutritious food that makes protein quality, vitamins, and some essential minerals (iron and zinc) more available. With the help of zero tillage, we can sow wheat at a minimum time after the harvest of paddy rice, by utilizing the moisture contents of rice straw for the germination of wheat. The aim of research was to compare these two sowing techniques for wheat production by considering the parameters like emerging rate index of wheat seed and crop yield along with some suitable statistical technique. The value of the moisture content was highest in zero tillage technique was 18.55%. On the other hand, the smallest value of the moisture content was found with conventional tillage system (16.59%). The highest value of the emergence rate index was found for zero tillage technique (14.11 %/day) and lowest value of the emergence rate index was found with conventional tillage technique was 11.8 %/day. The total dry biomass recorded was 420 g/m² for zero tillage and 360 g/m² for conventional tillage suggesting a greater potential for bioenergy applications. Therefore, zero tillage practices are more environmentally sustainable and beneficial for farmers compared to conventional tillage systems in the rice-wheat cropping system.